2005
DOI: 10.1371/journal.pgen.0030198.eor
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic pairing and segregation of achiasmate sex chromosomes in eutherian mammals: the role of SYCP3 protein

Abstract: In most eutherian mammals, sex chromosomes synapse and recombine during male meiosis in a small region called pseudoautosomal region. However in some species sex chromosomes do not synapse, and how these chromosomes manage to ensure their proper segregation is under discussion. Here we present a study of the meiotic structure and behavior of sex chromosomes in one of these species, the Mongolian gerbil (Meriones unguiculatus). We have analyzed the location of synaptonemal complex (SC) proteins SYCP1 and SYCP3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…Instead, we found that X and Y chromosomes can interact through conspicuous structural modifications of AEs: we observed SYCP3 filaments connecting sex chromosomes at late stages of prophase I, and some structural modifications are also detected between zygotene and diplotene . This situation resembles the case of the Mongolian gerbil and several species of marsupials in which asynaptic sex chromosomes present striking reorganizations of SYCP3 involved in their interactions (Solari and Bianchi 1975;Sharp 1982;Roche et al 1986;Seluja et al 1987;Page et al 2005;de la Fuente et al 2007). Therefore, our results in M. duodecimcostatus reinforce and extend the idea that SC components may act as common factors for the association of asynaptic sex chromosomes.…”
Section: Homologous Synapsis Heterologous Synapsis and Asynapsissupporting
confidence: 84%
See 3 more Smart Citations
“…Instead, we found that X and Y chromosomes can interact through conspicuous structural modifications of AEs: we observed SYCP3 filaments connecting sex chromosomes at late stages of prophase I, and some structural modifications are also detected between zygotene and diplotene . This situation resembles the case of the Mongolian gerbil and several species of marsupials in which asynaptic sex chromosomes present striking reorganizations of SYCP3 involved in their interactions (Solari and Bianchi 1975;Sharp 1982;Roche et al 1986;Seluja et al 1987;Page et al 2005;de la Fuente et al 2007). Therefore, our results in M. duodecimcostatus reinforce and extend the idea that SC components may act as common factors for the association of asynaptic sex chromosomes.…”
Section: Homologous Synapsis Heterologous Synapsis and Asynapsissupporting
confidence: 84%
“…In order to more precisely resolve the position of sex chromosomes during segregation, we used an antibody against γH2AX, a histone variant that is mainly located in the sex chromosomes at the end of prophase I and later on (de la Fuente et al 2007). Thus, we have confirmed the results of the SYCP3 signal in the sex chromosomes during the first meiotic division and the absence of chromatin connections between X and Y chromosomes during segregation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At mid-pachytene, the number of dots decreases, it being undetectable at late pachytene. Mlh1, a protein involved in the process of meiotic recombination, is detected at late pachytene on autosomal chromatid SCs, but it is absent on sex chromosomes (de la Fuente et al 2007).…”
Section: A Long History Of Sce During Meiosismentioning
confidence: 99%